Effect of dietary supplementation of sodium sulphite on ruminal fermentation in buffaloes - GARG, S L; NANGIA, O P (The Indian Journal of Animal Sciences, 2013)
Feeding sodium sulphite @ 100 glday for 3 weeks to buffaloes inhibited total volatile fatty acids productlon, depressed acetate and butyrate percentage and increased propionate per cent, decreased total ruminal nitrogen, ammonia nitrogen and microbial protein nitrogen. The in vitro fermentation ratc and net growth of rumen micro-organism decreased, while blood glucose level increased on sodium sulphite supplementation.